Development Strategies For Small-Scale Fisherman’s Madidihang Catch Records in Ambon City - Londah, Kimberly Olivia; Matrutty, Delly D.P.; Tawari, Ruslan H.S. (Agrikan Jurnal Agribisnis Perikanan, 2024)
The low level of logbook implementation seems to be due to the absence of intensive socialization and strict sanctions in the implementation of the ministerial regulation. The Indonesian government continues to increase its reach and utilization rate to all fishers. The accuracy of fishing data is needed to support fish resource management. So that the effort to design a more effective and efficient recording of catch records in the implementation of small-scale fishermen's Madidihang Tuna catch data recording becomes very urgent and absolutely necessary at this time in Ambon City. The purpose of this research is to formulate alternatives for the development of small-scale fishermen's Madidihang Tuna catch records in Ambon City. This research was conducted for 2 months, from July to August 2023, to find out the development strategy using SWOT analysis. The results of the SWOT analysis show that the S-O Strategy: Encourage small-scale fishers in recording catches and Improve the ability of small-scale fishers in compiling catch data, S-T Strategy: Build awareness of small-scale fishers regarding the benefits and importance of recording catches, W-O Strategy: Increase the socialization of catch recording to small-scale fishers and Encourage small-scale fishers to improve the use of catch recording software, W-T Strategy: Collaborate with 3rd parties to help small-scale fishers record their catches.